Mão de obra avulsa no Porto do Mucuripe: modernização e mudanças nas relações trabalhistas - Marinho, Nahyara Estevam (2021)
This thesis aims to analyze the changes that have taken place in the labor universe of self-employed dockworkers at Porto do Mucuripe, in Fortaleza, Ceará, which occurred after the implementation of the Port Modernization Law. This investigation focuses on the new configurations of labor relations of the TPAs, as they are also called, in the Brazilian neoliberal adjustment processes in the 1990s. A field research has been made, started at the Technological Vocational Center of Docas do Ceará company, at the intervals of the training course aimed at these workers, through written questionnaires, oral and recorded interviews, in addition to a field diary. In a second stage of the research, approaches to workers in union spaces were conducted, with a greater focus on narrative interviews recorded in audio. In parallel, theoretical research was carried out, with the aim of sociological analysis of the data, a bibliographical survey with the reading of already prepared works on the subject, and documentary research with labor conventions, letters and journalistic material already published. Factors that TPAs recognize as positive in the current configuration were identified, such as the popularization of the use of PPEs, increased egalitarian work assignments and accurate transfer of payments and benefits. Negligence with workers' health and the decrease in Port of Mucuripe’s ship traffic, with the construction of the Port of Pecém which contributed to workers being subjected to unfavorable negotiations, are some of the criticisms pointed out about the current conjuncture. Among negotiations, changes, benefits and losses, there is the struggle for power within the field of dock work. Therefore, I believe that the control over the various factors that make up the world of casual port labor, such as the management of labor, qualification and the form of accessing the profession, is being withdrawn from the hands of workers and transferred to port operator companies, through the Labor Management Agency. It is a restructuring process on several fronts, including the relationship between unions and workers. The Port Modernization Law and the transformations it caused constitute, together with other neoliberal measures taken at the 1990s in Brazil, a process of adjustment imposed on different countries, according to their position in the international division of labor. Such measures are based on the maintenance of capital accumulation in the economic financial regime, giving rise to a structural crisis that makes peripheral countries even more dependent on large economies, marked by instability and insecurity.